A CARE-compliant article: optical coherence tomography for epithelial basement membrane dystrophy. Issue 13 (March 2019) - Kuo, Yi-Chun; Lee, Yuan-Chieh
Abstract: Rationale: The etiology of anterior corneal opacities and the effect of debridement cannot be determined by biomicroscopy. Optical coherence tomography (OCT) helps identify the character and depth of these lesions. Patient concerns: A 45-year-old female complained of progressive blurred vision for a long time. Slit lamp biomicroscopy showed irregular, faint scar-like opacity of anterior cornea in her both eyes. Pentacam Scheimpflug camera tomography showed irregular astigmatism of anterior corneal surface. Anterior segment spectral-domain OCT revealed thickened, hyper-reflective linings, and scattered lesions, mainly in the epithelial layer. Diagnoses: Epithelial basement membrane dystrophy (EBMD). Intervention: Epithelial debridement and bandage lenses. Outcomes: The cornea became clear and the vision improved soon after debridement. The pathology showed thickened aberrant basement membrane extending into mid-epithelial layer, with microcyst-like lesions also noted. Lessons: OCT defines the depth of lesions and helps diagnosis and management of EBMD.